Measuring usability of electronic Quran mobile application in pervasive computing environments: user profiling - Abd Ghani, Nur Nina Syazwani; Omar, Ridha; Mahmud, Murni (UNITEN, 2017)
This study is aimed at identifying and examining the most frequent functions or tasks applied when using popular electronic Quran (or e-Quran) mobile applications. The main investigative instrument utilized in this study was questionnaire, whilst the data analysis process was accomplished using the descriptive statistical method of SPSS. Based on the analysis, two most popular e-Quran apps have been identified, and three most frequent functions used have also been ascertained. The outcome of this study will form the basis of future usability and User Experience evaluation of e-Quran application.